Sialis primitivus sp. nov. (Megaloptera: Sialidae), a remarkable new alderfly species from China - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2015)
A new species of the alderfly, Sialis primitivus sp. nov. from China is described. Remarkably, the general habitus of the new species resembles the New World genera Protosialis van der Weele, 1909 and Ilyobius Enderlein, 1910 as well as the Madagascan endemic genus Haplosialis Navás, 1927 by having similar wing venation. However, the characteristics of mouthparts and genitalia indicate the new species belongs to Sialis and probably represents the basalmost species among all known extant Sialis species.